(x-3+2i)(x-3-2i)=0

Simple and best practice solution for (x-3+2i)(x-3-2i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3+2i)(x-3-2i)=0 equation:


Simplifying
(x + -3 + 2i)(x + -3 + -2i) = 0

Reorder the terms:
(-3 + 2i + x)(x + -3 + -2i) = 0

Reorder the terms:
(-3 + 2i + x)(-3 + -2i + x) = 0

Multiply (-3 + 2i + x) * (-3 + -2i + x)
(-3(-3 + -2i + x) + 2i * (-3 + -2i + x) + x(-3 + -2i + x)) = 0
((-3 * -3 + -2i * -3 + x * -3) + 2i * (-3 + -2i + x) + x(-3 + -2i + x)) = 0
((9 + 6i + -3x) + 2i * (-3 + -2i + x) + x(-3 + -2i + x)) = 0
(9 + 6i + -3x + (-3 * 2i + -2i * 2i + x * 2i) + x(-3 + -2i + x)) = 0

Reorder the terms:
(9 + 6i + -3x + (-6i + 2ix + -4i2) + x(-3 + -2i + x)) = 0
(9 + 6i + -3x + (-6i + 2ix + -4i2) + x(-3 + -2i + x)) = 0
(9 + 6i + -3x + -6i + 2ix + -4i2 + (-3 * x + -2i * x + x * x)) = 0

Reorder the terms:
(9 + 6i + -3x + -6i + 2ix + -4i2 + (-2ix + -3x + x2)) = 0
(9 + 6i + -3x + -6i + 2ix + -4i2 + (-2ix + -3x + x2)) = 0

Reorder the terms:
(9 + 6i + -6i + 2ix + -2ix + -4i2 + -3x + -3x + x2) = 0

Combine like terms: 6i + -6i = 0
(9 + 0 + 2ix + -2ix + -4i2 + -3x + -3x + x2) = 0
(9 + 2ix + -2ix + -4i2 + -3x + -3x + x2) = 0

Combine like terms: 2ix + -2ix = 0
(9 + 0 + -4i2 + -3x + -3x + x2) = 0
(9 + -4i2 + -3x + -3x + x2) = 0

Combine like terms: -3x + -3x = -6x
(9 + -4i2 + -6x + x2) = 0

Solving
9 + -4i2 + -6x + x2 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -4i2 + -6x + -9 + x2 = 0 + -9

Reorder the terms:
9 + -9 + -4i2 + -6x + x2 = 0 + -9

Combine like terms: 9 + -9 = 0
0 + -4i2 + -6x + x2 = 0 + -9
-4i2 + -6x + x2 = 0 + -9

Combine like terms: 0 + -9 = -9
-4i2 + -6x + x2 = -9

Add '6x' to each side of the equation.
-4i2 + -6x + 6x + x2 = -9 + 6x

Combine like terms: -6x + 6x = 0
-4i2 + 0 + x2 = -9 + 6x
-4i2 + x2 = -9 + 6x

Add '-1x2' to each side of the equation.
-4i2 + x2 + -1x2 = -9 + 6x + -1x2

Combine like terms: x2 + -1x2 = 0
-4i2 + 0 = -9 + 6x + -1x2
-4i2 = -9 + 6x + -1x2

Divide each side by '-4'.
i2 = 2.25 + -1.5x + 0.25x2

Simplifying
i2 = 2.25 + -1.5x + 0.25x2

Reorder the terms:
-2.25 + i2 + 1.5x + -0.25x2 = 2.25 + -1.5x + 0.25x2 + -2.25 + 1.5x + -0.25x2

Reorder the terms:
-2.25 + i2 + 1.5x + -0.25x2 = 2.25 + -2.25 + -1.5x + 1.5x + 0.25x2 + -0.25x2

Combine like terms: 2.25 + -2.25 = 0.00
-2.25 + i2 + 1.5x + -0.25x2 = 0.00 + -1.5x + 1.5x + 0.25x2 + -0.25x2
-2.25 + i2 + 1.5x + -0.25x2 = -1.5x + 1.5x + 0.25x2 + -0.25x2

Combine like terms: -1.5x + 1.5x = 0.0
-2.25 + i2 + 1.5x + -0.25x2 = 0.0 + 0.25x2 + -0.25x2
-2.25 + i2 + 1.5x + -0.25x2 = 0.25x2 + -0.25x2

Combine like terms: 0.25x2 + -0.25x2 = 0.00
-2.25 + i2 + 1.5x + -0.25x2 = 0.00

The solution to this equation could not be determined.

See similar equations:

| 3b^2-11b^2+14b^2= | | 1=m+10/26 | | 4+(5+6)=(4+5)+6 | | n/2+9=11 | | -7(2x+5)= | | -1=-5+v+3 | | 2+5=5+2 | | 18=-8x+34 | | x/3-8=-3 | | 3m+5(6-m)=4 | | 3m+5m(6-m)=4 | | 4y-5+y+31=8y+30-5y | | 8r^2-2r+1=0 | | 19=v+7/2 | | a-20/10=-5 | | -4(n-1)-5n= | | 93=c+32 | | w^2-7w-7=0 | | -12+4r=2(r-3) | | 8r^2-0.02r+0.01=0 | | 4=x/5+1 | | 0.08r^2-0.02r+0.01=0 | | -490x^2+75x+12=0 | | 4(3.7)-2y=-20 | | 0.02r-0.01=0.08r^2 | | 14+n/11=12 | | -38x+28=172 | | X^2+18x-16=0 | | -19=n-8/2 | | 3y^2-26y+35=0 | | -10x+14=32 | | -10+p/3=3 |

Equations solver categories